The DNA mismatch repair protein, MSH6 is a novel regulator of PD-L1 expression - Kirsten Brooksbank; Charlotte Smith; Eleni Maniati; Amy Gibson; Wai Yiu Tse; Amy Kate Hall; Jun Wang; Tyson V Sharp; Sarah A Martin (Neoplasia: An International Journal for Oncology Research)
Immune checkpoint inhibitors (ICIs) are extremely effective in a subgroup of mismatch repair-deficient (MMRd) cancers, but ∼50% remain resistant to treatment. We have shown for the first time that this may be due to the differential regulation of factors linked to response to ICIs upon loss of the different MMR genes. Here, we show that increased PD-L1 expression is observed upon loss of the MMR genes MLH1, MSH2 and PMS2. However, this is not true upon loss of MSH6, and we show that this is due to a novel role for MSH6 as a direct regulator of PD-L1 transcription, dependent on recruitment by the histone trimethyltransferase SETD2. Next-generation sequencing of MLH1 and MSH6 knockout (KO) cells revealed that MSH6 KO cells have significantly lower microsatellite instability in comparison to MLH1 KO cells, despite MSH6 KO cells having a higher mutational burden. These findings emphasise the need for gene-specific stratification in the MMRd cohort.